in Word Problem Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

4x+3y=x²-xy, so 3y+xy=x²-4x, y(x+3)=x²-4x, y=(x²-4x)/(x+3).

4x+3y=8, so, substituting for y, 4x+3(x²-4x)/(x+3)=8.

Multiply through by x+3:



Using the quadratic formula: x=(8±√(64+672))/14=(8±√736)/14=(4+2√46)/7 or (4-2√46)/7.

So y=(8-4x)/3=(40-8√46)/21 or (40+8√46)/21.

So there are two (x,y) solutions: ((4+2√46)/7,(40-8√46)/21) or ((4-2√46)/7,(40+8√46)/21).

That is, (2.5092,-0.6790) or (-1.3664,4.4885) approx.

by Top Rated User (782k points)

Related questions

1 answer
asked Jul 14, 2015 in Algebra 1 Answers by anonymous | 260 views
1 answer
asked Nov 17, 2013 in Pre-Algebra Answers by Wendy Hoi | 197 views
1 answer
1 answer
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
85,304 questions
90,721 answers
101,121 users